Perancangan Maskot Sebagai Strategi Brand Activation Klub Sepakbola PSIM Jogja - Ditya Rizkizha (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2019)
Yogyakarta, a town still exist will including its culture and tradition, have a football team local named PSIM Jogja. Identity PSIM Jogja attaching with blue and white, and Tugu Jogja to represent the club it comes from the town of Jogja. This can be seen through logo. PSIM Jogja have the logo club, classic it is meaningful. Historically the club PSIM cannot be separated by means of Keraton Jogja. But, to nickname attaching in PSIM Jogja itself is not the point where the brand image. Several media often mentioned differently. This has touched frequently make a question ask mind forces loyal to PSIM Jogja. Of a question that need of the effort to create and strengthened image PSIM Jogja through a strategy of branding called brand activation. See this difficulty researchers consider mascot design as part of its brand activation done to realize vision and the mission of PSIM Jogja as a football club “Warisane Simbah”, this business also to care for existence PSIM Jogja in various football Indonesia and close the club with audience.